PENGEMBANGAN MEDIA BINGKAI BERGAMBARDENGAN TEMA KONDISI GEOGRAFIS DAN MATA PENCAHARIAN UNTUK PEMBELAJARAN IPS DI MI KELAS IV - Edy Musthofa (Khazanah Pendidikan, 2020)
ABSTRACTThis study aims to produce picture frame learning media with the theme ofgeographical conditions and livelihoods activity for social studies learning for 4thgrade of elementary School. This study also aims to determine the instructional mediadecent picture frame for social study learning for 4th grade of elementary School basedon media validation by matter expert, media validation by media expert, the test mediause by teachers and students. This research iscategorized as ResearchandDevelopment(R &D). The studywas conductedwithseveralstages such as, the datacollection stage, the planningstage, development stage, as well asthe mediavalidationandtestmedia use. Data collection instrumentsused inthisresearchisthe development ofaquestionnaire. Datawere obtainedfromthe results ofthe mediavalidation bya matterexpert, the results ofthemedia validationbya mediaexpert, the results of test media usebyateacher, andthe results of test media use by fourelementary School studentsof 4thgrade. The data obtained wereconvertedinto likertscale todeterminethe categoryofpictureframe learning media. It is worthy tobe usedwhen media validation by matterexperts, media validationbymediaexperts, testmedia usebyteachersandstudentshas agood mean score ofminimumcategory. The results of the research of “Produce PictureFrame Learning Media with The Theme of Geographical Conditions and LivelihoodsActivity for Social Studies Learning for 4th Grade”, considered worthy to use in socialstudies learning. It can be seen from the results of the media validation by matterexperts who have an average final score of 4.3; results of the validation media bymedia experts have an average final score of 3.7; test media use by teacher had amean score of 4.85; test media use by students has the lowest mean score of 3.7 andthe highest mean score of 4.85 and had class mean score of 4.51. From the results itappears that the average instructional picture frame media is worthy to be used forsocial studies learning with good quality.Keywords:pictureframe learning media,social studies learning.